Language Exploration in the Framework of Existentialism - Anisa, Rizka; Sahayu, Wening; Nurhayati, Lusi (Humanus, 2025)
Language has always been one of the most influential and important aspects of human life, both as a medium of communication and a tool to shape identity, communicate meaning, and deal with the uncertainties of life. In existentialism, language is used as a tool to question freedom, responsibility, and the essence of the human condition. The researcher investigated constructions related to “existentialism” through an interview with a multilingual student whose experiences illustrate many aspects of the phenomenon. Language in existentialism, examines language as a way for humans to seek meaning in life, express identity, and deal with the absurd. This research utilizes the narrative inquiry method and focuses on the experience of one participant whose narrative details language choices influenced by emotional needs, reflection, and social interaction. The findings illustrate language as a form of self-reflection, emotional activation and liberation. Using a foreign language can create emotional distance and allow for a higher degree of freedom due to less cultural pressure. The reflection of moral responsibility in communication for the effects it causes provides insight into how language influences human mindsets and information processing.